갑상선 자가항체와 만성 특발성 두드러기의 예후 - 이서영; 송우정; 정재우; 박흥우; 조상헌; 민경업; 강혜련 (Allergy asthma & respiratory disease, 2013)
Purpose: Chronic urticaria is a common disease, but clinically, it is not easy to treat and predict the prognosis since the causes and pathophysiology of chronic urticaria remain unknown. Many studies have been done that defined the association between chronic urticaria and thyroid autoimmunity. However, the clinical role of antithyroid antibodies (ATAs) has not been fully evaluated. Methods: We retrospectively reviewed the medical records of patients with chronic urticaria and compared the duration of treatment, the frequency of steroid use, and the level of medications used in the treatment of urticaria according to the presence or absence of ATAs including the antithyroglobulin (anti-TG) antibody, antithyroid peroxidase antibody, and antithyrotropin-stimulating hormone receptor antibody. Results: A total of 194 patients with chronic urticaria was enrolled; of which, 108 patients were free of ATAs and 86 patients had at least one ATA. The treatment duration was significantly longer in the anti-TG antibody-positive patients compared to the patients without ATAs (39.6±10.2 months/18.0±3.4 months, P=0.02). The patients with the anti-TG antibody also showed more frequent steroid use than that of the patients without the anti-TG antibody (2.1±0.4/1.1±0.3, P=0.05). The level of medications used to achieve control of urticaria tended to be higher in patients with the anti-TG antibody than in the ATA-negative patients group. Conclusion: From this study, we suggest that the evaluation of thyroid autoantibodies, especially the anti-TG antibody, can be a useful tool in predicting the prognosis and making decisions for the treatment strategy of patients with chronic urticaria. KCI Citation Count: 6